Investigating the Method of Da’wah and the Role of Political-Economy of Jemaah Tarbiyah in Urban Malang Society - A'isyah A'isyah; Zulkipli Lessy (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2022)
Since the emergence of the overwhelming electoral vote for Partai Keadilan Sejahtera (Prosperous Justice Party) in the 2019 legislative election in Malang City, we discovered the impact of political-economy of Jemaah Tarbiyah on the urban society is a significant boost in electability for PKS. The subject selected is an Islamic philanthropic organisation, Ash-Shahwah Foundation (YASA) in Malang City as the sympathisers of Jemaah Tarbiyah. The supportive factors for regulating the political economy of Jemaah Tarbiyah include the method, role, and participation of YASA in Malang City. Through the method of da’wah, the figure of Jemaah Tarbiyah, Abu Haidar, stated that shalat is the key to success in life, and this has been successfully gaining hundreds of members. The role of YASA is to educate the urban society that obligatory alms become a lifestyle for their charitable politics. YASA becomes an intermediary to the connection of elite-mass or mustahiq-cadres’ relationships for gaining trust and getting massive electoral votes. The urban society participation, particularly the benefactors, can be seen from their enthusiasm in donating their wealth and demonstrating solidarity among individuals to strengthen informal religious learning courses in mosques. Findings show that the political economy of Jemaah Tarbiyah initiated the great success of gaining substantial electoral votes through philanthropic practices used as indirect support and funding for election campaigns. Notably, there is a political tendency for YASA to change its paradigm of philanthropic practice, for which the initial goal was to raise humanitarian aid and charitable funds and to shift funds toward financing a campaign.